Approximating a harmonizable isotropic random field. (2001) - Swift, Randall J.
Abstract : The class of harmonizable fields is a natural extension of the class of stationary fields. This paper considers a stochastic series approximation of a harmonizable isotropic random field. This approximation is useful for numerical simulation of such a field.